Ebola: Lessons from a human tragedy. Issue 6 (December 2015) - Majumder, Maimuna (Maia)
Abstract : The West African Ebola outbreak brought death and disruption on an unprecedented scale. But in its wake comes new knowledge to help model and respond to future epidemics.Maimuna Majumder reports